The use of esketamine sedation in the emergency department for manipulation of paediatric forearm fractures: A 5 year study. Issue 6 (June 2021) - Patel, Dhawal; Talbot, Christopher; Luo, Weisang; Mulvaney, Shirley; Byrne, Eileen
Highlights: Over a 5 year period, on assessment of 151 paediatric forearm fractures, 89.1% were managed definitively using esketamine sedation. All patients requiring further surgery had a cast index greater than 0.8. No adverse events occurred following administration of esketamine. An overall non adjusted cost saving of £318, 300 was made over the 5 year study period to the NHS. Abstract: The purpose of this study is to assess the use of esketamine as procedural sedation for the reduction of paediatric forearm fractures in the emergency department (ED). A retrospective analysis was undertaken of forearm fractures between 1 st January 2012 to 31 st December 2016 which were treated with manipulation in ED using esketamine sedation. Patient demographics and fracture configuration were collected. Patient radiographs were evaluated and cast index calculated. 151 patients (103 male, 48 female) were included (average age of 8.5 [1 to 15]). Four (2.6%) patients were lost to final follow up. 11 (7%) fractures were not accepted after initial manipulation and required formal surgical management under general anaesthetic. At one week follow up, a further 5 (3%) fractures displaced requiring operative management. 100% of patients who slipped at one week had a cast index greater than 0.8 [average 0.86, 95% CI 0.80-0.92]. At final follow up successful reduction was achieved in 89.1% (131/144) of patients. No adverse events occurred following administration of esketamine. This study provides evidence that manipulation of paediatric forearm fractures using esketamine as procedural sedation in the ED is comparable to other methods in achieving acceptable outcomes. This is in addition to the potential for cost savings. However, future studies formally assessing cost effectiveness and patient outcomes are needed.